The changing rationale for governance choices: Early vs. late adopters of global services sourcing. (16th April 2018) - Manning, Stephan; Massini, Silvia; Peeters, Carine; Lewin, Arie Y.
Abstract : Research Summary: This article studies how the logic of firm governance choices varies as a function of the time of adoption of particular sourcing practices. Using data on the diffusion of global business services sourcing as a management practice from early experiments in the 1980s through 2011, we show that the extent to which governance choices are affected by process commoditization, availability of external service capabilities, and past governance choices depends on whether firms are early or late adopters. Findings inform research on governance choice dynamics specifically in highly diverse and evolving firm populations. Managerial Summary: This article considers how firms have chosen delivery models in global services sourcing decisions over time. Based on comprehensive data, we make two major observations. First, we find that firms that began with global services sourcing early, invested mainly in their internal sourcing capacity, while outsourcing only simple tasks to external providers, whereas firms that started later invested more in their capability to outsource various services to increasingly sophisticated suppliers. Second, we find that initial investments in internal or external sourcing capabilities have a strong effect on future choices of delivery models. This explains why, even today, firms vary greatly in how they implement global sourcing decisions, and it suggests that newcomers should learn from their own peer group rather than from highly experienced firms.